RELATIONSHIP OF FAMILY SUPPORT WITH QUALITY OF LIFE OF HEMODIALIZED PATIENTS USING STUDY LITERATURE REVIEW METHOD - Hulu, Titusman; Budi, Nanang Prasetyo; Sari, Rina Puspita (Journal of Vocational Nursing, 2021)
Background : Hemodialysis is one of the therapies for Chronic Kidney Failure (CKD) patients. This process takes place on an ongoing basis which is closely related to the quality of life. Quality of life is strongly influenced by family support. One form of family support is emotional support which includes forms of affection, trust, attention, assistance during therapy. With this support, it affects patient compliance with therapy programs and medical treatment programs so that it will improve the patient's quality of life. Objective: To determine the relationship between family support and quality of life of hemodialysis patients. Based on journals that have been analyzed by researchers using a literature review research design or literature review study literature review Methods: search for this research article through four databases, namely Google Scholar, ProQuest, EBSCO, and PubMed using keywords and inclusion criteria, namely 21 journal using Indonesian and English, the type of article publication is full-text articles, original research articles, articles that have ISSN and DOI, the theme of the article is the relationship of family support with the quality of life of hemodialysis patients, in the 2016-2021 period with the literature review method. Results: The results of this study showed a significant relationship between family support and quality of life of hemodialysis patients with p-value=0,001 <a=0.05 with a positive correlation direction with low correlation strength. Conclusion: The higher the support from the family, the better the quality of life for chronic kidney failure patients undergoing hemodialysis.